BIDIL: A RACE-TARGETED DRUG FOR BLACK AMERICAN’S ONLY - Talniya, Naveen Chandra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â It has been noted that pharma research toward race-targeted medicine and it criticism is going on simultaneously over the past few years. Some argued that drugs specifically target to cure particular racial groups could play a vital role against racial disparities in health. While others claimed that race-targeted medicine inappropriately treats race as a biological reason for racial disparities when broader social and environmental factors may offer better descriptions. Much of this debate includes the Food and Drug Administration's approval of drug BiDil in 2005, which became the first drug to be marked for a specific racial group black Americans who suffers from heart failure (HF). This controversial drug was declared failed due to less attention of physician's as well as its high cost in market. The highlighted part of this review is that besides much criticism still this drug prescribed by majority of physicians. Moreover, BiDil is not only one which is race specific but also there are more drugs which have been claimed to have different effects in different racial or ethnic groups. Â 